The cave rocky relief of the Dimnice cave - Slabe, Tadej (Annales. Series historia naturalis, 1997)
The rocky relief cave passage surfaces helps to explain a complex genesis of aponor cave. In this cave traces of the oldest water flow that had shaped the passages are preserved, the traces of faster streams flowing above the gravel and the water which shaped the rock surfaces as it flowed above the fine-grained sediments that filled up the cave. Today the water flow is found in the lower passage and the cave is shapped by the water that trickles down the walls of the entrance shaft and by the humidity due to strong air circulation. Slight weathering of the rock surfaces and flowstone is due to well-pronounced microclimatic conditions in this cave.
Keywords: Dimnice; Istra; Istria; karst; Kras; krasoslovje; reliefi; Slovenia; Slovenija; speleologija